2009
DOI: 10.5194/acp-9-2007-2009
|View full text |Cite
|
Sign up to set email alerts
|

Carbonaceous aerosols in Norwegian urban areas

Abstract: Abstract. Little is known regarding levels and source strength of carbonaceous aerosols in Scandinavia. In the present study, ambient aerosol (PM 10 and PM 2.5 ) concentrations of elemental carbon (EC), organic carbon (OC), waterinsoluble organic carbon (WINSOC), and water-soluble organic carbon (WSOC) are reported for a curbside site, an urban background site, and a suburban site in Norway in order to investigate their spatial and seasonal variations. Aerosol filter samples were collected using tandem filter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 62 publications
6
35
0
1
Order By: Relevance
“…wood type, type of appliance and flaming versus smoldering combustion, and consequently between geographical regions, we have allowed for a rather wide range in our calculations and adopted the range and approach reported by Yttri et al (2011a) (Tables 1 and 2). Consequently, the analytical method used to determine levoglucosan is self-consistent, as the method by Dye and Yttri (2005) was applied both in the present study as well as in that of Yttri et al (2009), from which the emission ratio range listed in Yttri et al (2011a) was derived.…”
Section: Emission Ratios Used To Calculate Ec From Biomass Burning (Ementioning
confidence: 99%
“…wood type, type of appliance and flaming versus smoldering combustion, and consequently between geographical regions, we have allowed for a rather wide range in our calculations and adopted the range and approach reported by Yttri et al (2011a) (Tables 1 and 2). Consequently, the analytical method used to determine levoglucosan is self-consistent, as the method by Dye and Yttri (2005) was applied both in the present study as well as in that of Yttri et al (2009), from which the emission ratio range listed in Yttri et al (2011a) was derived.…”
Section: Emission Ratios Used To Calculate Ec From Biomass Burning (Ementioning
confidence: 99%
“…Water soluble compounds were removed washing portions of the high volume sampled filters using MilliQ (Millipore) water. Each portion of the filter was placed in a filtration assembly -similar to the one reported by Yttri et al (2009) suitably designed for this application. The washed area was 37 mm diameter wide (i.e.…”
Section: Washing Proceduresmentioning
confidence: 99%
“…For urban environments, Zdráhal et al (2002) estimated that wood burning emissions accounted for ∼35% of organic carbon (OC) in Ghent, Belgium, during a winter episode. Caseiro et al (2009), Yttri et al (2009) and Szidat et al (2006) also reported high contributions of wood burning organics to OC in Vienna (Austria), Oslo (Norway) and Zürich (Switzerland), i.e., ∼20%, ∼30% and ∼40% respectively for winter time at urban background sites. Finally, Favez et al (2009) suggested that residential wood burning emissions account for about 20±10% of total PM 2.5 in such a large city as Paris, France, during wintertime.…”
Section: Introductionmentioning
confidence: 99%